Investigations of physicochemical properties of dusts generated in mechanical reclamation process of spent moulding sands with alkaline resins - R. Dańko; M. Holtzer; J. Dańko (China Foundry, 2014)
Mechanical reclamation processes of spent moulding sands generate large amounts of post-reclamation dusts mainly containing rubbed spent binding agents and quartz dusts. The amount of post-reclamation dusts, depending in the reclamation system efficiency and the reclaim dedusting system, can reach 5%-10% in relation to the total reclaimed spent moulding sand. The proper utilization of such material is a big problem facing foundries these days. This study presents the results of investigations of physicochemical properties of post- reclamation dusts. All tested dusts originated from various Polish cast steel plants applying the mechanical reclamation process of moulding sands with alkaline resins, obtained from different producers. Different dusts, delivered from foundries, were tested to determine their chemical composition, granular characterization, physicochemical and energetic properties. Presented results confirmed assumptions that it is possible to utilize dusts generated during mechanical reclamation of used sands with organic resins as a source of energy.